2021
DOI: 10.3389/fpsyg.2021.752564
|View full text |Cite|
|
Sign up to set email alerts
|

The Interplay Between Quality of Life and Resilience Factors in Later Life: A Network Analysis

Abstract: Age-related challenges and transitions can have considerable social, psychological, and physical consequences that may lead to significant changes in quality of life (QoL). As such, maintaining high levels of QoL in later life may crucially depend on the ability to demonstrate resilience (i.e., successful adaptation to late-life challenges). The current study set out to explore the interplay between several resilience factors, and how these contribute to the realization and maintenance of (different facets of)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 139 publications
1
6
1
Order By: Relevance
“…The dimension scores obtained in this study were like the scores of the WHOQOL-OLD Turkish validation study (2) and were lower than the scores obtained in developed societies (12)(13)(14), whereas closer dimension scores were obtained with the other developing countries such as India, Iran, Brazil, and Mexico (15)(16)(17)(18). When we compared the dimension scores obtained from this study with the findings of the multicenter international development study published by Power et al (1), the mean dimension scores we obtained were lower than the scores obtained from the international study in all dimensions except the intimacy dimension, which is about the same as in the development study.…”
Section: Discussioncontrasting
confidence: 61%
“…The dimension scores obtained in this study were like the scores of the WHOQOL-OLD Turkish validation study (2) and were lower than the scores obtained in developed societies (12)(13)(14), whereas closer dimension scores were obtained with the other developing countries such as India, Iran, Brazil, and Mexico (15)(16)(17)(18). When we compared the dimension scores obtained from this study with the findings of the multicenter international development study published by Power et al (1), the mean dimension scores we obtained were lower than the scores obtained from the international study in all dimensions except the intimacy dimension, which is about the same as in the development study.…”
Section: Discussioncontrasting
confidence: 61%
“…The findings demonstrated that the initial half of the data collection time yielded lower quality of life than the second half. Therefore, it could be suggested that people became increasingly resistant to the pandemic situation and restriction changes over time, possibly because they had coped with the pandemic-related events and got accustomed to the uncertainty and frequent policy changes [ 36 ]. Similarly, recent findings reported poor QoL in earlier waves of the pandemic compared to late pandemic, indicating that adapting to changes in daily life has reduced the anticipated impact on Qol over time [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another way is through educational programs aimed at fostering coping abilities and self-management skills ( 29 , 36 ). Implementation of the resilience theory in geriatric research, however, requires the use of more integrated measures of the aging process, to indicate functional abilities of older individuals, and more comprehensive methods of research, to represent the complex relationships among involving factors ( 37 , 38 ).…”
Section: Introductionmentioning
confidence: 99%